You Can’t Beat Relating with God for Spiritual Well-Being: Comparing a Generic Version with the Original Spiritual Well-Being Questionnaire Called SHALOM - Fisher, John (Religions, 2013)
The Spiritual Health And Life-Orientation Measure (SHALOM) is a 20-item instrument that assesses the quality of relationships of the respondent with self, others, the environment and/or a Transcendent Other. In the Transcendental domain, four of the five items had the words ‘God, ‘Divine’ and ‘Creator’ replaced by the word ‘Transcendent’ to make the survey more generic by removing any implied reference to any god or religion. Invitations to complete a web survey were sent to people who had published papers in spirituality, or belonged to associations for spirituality or religious studies, as well as the Australian Atheist Forum. 409 respondents from 14 geographic regions, completed the survey. Confirmatory factor analysis revealed that the modified, generic form of SHALOM showed acceptable model fit, comprising four clearly delineated domains of spiritual well-being. The paper analyses the results derived from using the modified, generic version and, in comparison with results of applications of the original survey instrument, concludes with discussion of the comparative utility of each of the versions of SHALOM. Further studies with more people are warranted, but, from evidence presented here, it looks like you can’t beat relating with God for spiritual well-being.